2022
DOI: 10.3389/fenrg.2022.955875
|View full text |Cite
|
Sign up to set email alerts
|

Solving stochastic hydro unit commitment using benders decomposition and modified stochastic dual dynamic programming

Abstract: This paper proposes a stochastic hydro unit commitment (SHUC) model for a price-taker hydropower producer in a liberalized market. The objective is to maximize the total revenue of the hydropower producer, including the immediate revenue, future revenue (i.e., opportunity cost), and startup and shutdown cost. The market price uncertainty is taken into account through the scenario tree. The solution of the model is a challenging task due to its non-convex and high-dimensional characteristics. A solution method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…, j 1, 2, 3., J, and F β (Q d , α d ) can be converted into a linear function and linear constraint (Li et al, 2022).…”
Section: Solving Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…, j 1, 2, 3., J, and F β (Q d , α d ) can be converted into a linear function and linear constraint (Li et al, 2022).…”
Section: Solving Methodsmentioning
confidence: 99%
“…Where: Q d is the energy portfolio of the hydropower plant on operating day d, d 1, 2, 3, ., D, and D 30; E(Q d ) is the income function (Wang et al, 2005) of the energy portfolio, as shown in Eq. 2; F β (Q d , α d ) is the CVaR-based risk function (Li et al, 2022) of the energy portfolio, as shown in Eqs 10-11; λ d is the risk aversion coefficient, calculated as in Eq. 5.…”
Section: Upper Layer Objective Functionmentioning
confidence: 99%
See 1 more Smart Citation